Analisis Numerik Pengaruh Beban Hujan dan Gempa pada Stabilitas Lereng Tanah Tak Jenuh - Koven, Wilson; Hamdany, Abdul Halim (Institut Teknologi Bandung, 2024)
Abstract Rain and earthquake affect the stability of the slope. Rain results in infiltration on the slope which causes a decrease in negative pore water pressure on the slope and increases the groundwater level. Meanwhile, the seismic load from earthquake causes deformation on the slopes. Slope will experience even more critical condition if the effects of rain and earthquake are combined. This study aims to determine the influence of rain followed by earthquake on the stability of the unsaturated slope. This study consists of two stages of numerical analysis, which are seepage analysis to determine changes in pore water pressure on the slope and followed by non-linear time history dynamic analysis to calculate the deformation that occurs due to the ground motion. The soil-water characteristic curve from the field measurement will be incorporated in the upper layer of unsaturated soil and the Loma Prieta (1989) earthquake acceleration recording will be used. Six scenarios of rain followed by earthquake will be analyzed and compared, which are the scenario of rain intensity not changing for three days, the scenario of rain intensity gradually increasing and decreasing gradually, and the scenario of random rain intensity.